(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
One such Global effort, after the Alma Ata Declaration of 1978 which “called for the building of health systems that would provide comprehensive care, would be integrated, organized to promote equity, and would be driven by community needs”, is the emphasis on Universal Health Coverage (Sengupta, 2013). The World Health Organization Director General Margret Chan has claimed it to be “the most powerful concept that Public Health has to offer”. The World Health Report of 2010 defines it to be ‘an approach to finance health expenditure’ that serves to contain, reduce and finally eliminate out of pocket expenditure. It is usually explained using a cube whose length, breadth and height represent who to cover, how many services to be covered and how much of the total expenditure to be covered respectively. Rapid growth on all these three axes is considered to be the goal of public health policy. According to Oxfam, “WHO has been explicit that countries should prioritize four key actions to finance UHC reduce out-of-pocket payments, maximize mandatory pre-payment, establish large risk pools, and use general government revenue to cover those who cannot afford to contribute” (Oxfam Briefing Paper, 2013).